PENGALAMAN PENDONOR DALAM MEMBERIKAN DONOR DARAH DI KOTA PADANGSIDIMPUAN - Nina Nazlina; Adi Antoni; Abdullah AA; Juni Andriani Rangkuti; Nefonafratilova Ritonga; Maharani Dalimunthe; Septi Ariona; Rido Hasibuan; Putri Efrina Sahri Pulungan (Maternity and Neonatal : Jurnal Kebidanan, 2023)
The main problem that is often experienced by the public is due to lack of knowledge and low public awareness of the benefits and importance of blood donation among the wider community in general, blood transfusion is an activity process carried out in the transmission of donor blood to the recipient must meet the criteria and have certain conditions. which must be fulfilled. This research aims to dig deeper into the experiences of blood donors in providing blood donations. This research took place in Padangsidimpuan City. This type of research is qualitative with a phenomenological design. The number of participants in this research was 4 participants. With collaizzi techniques and thematic analysis. The results of this research obtained 3 themes and 8 sub-themes, Theme 1 Motivation for blood donation received sub-themes including (1) helping others, (2) moral satisfaction, (3) reducing the risk of disease. Theme 2 Motivation for blood donation has sub-themes including (1) Feeling satisfied, (2) Feeling tired, (3) Experiencing pain. Theme 3 Motivation for blood donation has sub-themes including (1) Increasing social awareness, (2) Increasing self-confidence